2021
DOI: 10.1002/tea.21679
|View full text |Cite
|
Sign up to set email alerts
|

Content knowledge and social factors influence student moral reasoning about CRISPR/Cas9 in humans

Abstract: Consideration of socioscientific issues (SSIs) promotes the development of moral and sociocultural perspectives that encourage a rich understanding of the nature of science. The use of moral reasoning to approach SSIs is known to influence how students justify arguments and persuade others; less is known about how student moral reasoning is influenced by both content knowledge and demographic identities. We performed an exploratory study to investigate how students use moral reasoning when considering an SSI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 89 publications
1
9
0
2
Order By: Relevance
“…Studies in the field of science and science education at the higher education level include: both male and female students commonly believed that issues of gender were restricted to the the male‐dominated science disciplines but female students are more persistent in studying science (Fisher et al., 2020); conceptual changes to SSI‐based obesity (Leung & Cheng, 2020); an effective intervention in science class with a taxonomy code (Newton & Zeidler, 2020); motivation to learn physics and chemistry influenced by academic majors (Salta & Koulougliotis, 2020); a study of teacher candidates that showed a lack of consistency, simplicity and completeness in the explanations given to students (Viennot, 2020); student literacy skills that are enhanced by the context of the task and still use a lot of pre‐interpreted texts (Lennox et al., 2020); teacher candidates implementing NOS in inquiry even though NOS is not required (Librea‐carden et al., 2021); content knowledge and social factors influencing students' moral reasoning (Seiter & Fuselier, 2021); and negotiations in scientific arguments producing group consensus (Governor et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the field of science and science education at the higher education level include: both male and female students commonly believed that issues of gender were restricted to the the male‐dominated science disciplines but female students are more persistent in studying science (Fisher et al., 2020); conceptual changes to SSI‐based obesity (Leung & Cheng, 2020); an effective intervention in science class with a taxonomy code (Newton & Zeidler, 2020); motivation to learn physics and chemistry influenced by academic majors (Salta & Koulougliotis, 2020); a study of teacher candidates that showed a lack of consistency, simplicity and completeness in the explanations given to students (Viennot, 2020); student literacy skills that are enhanced by the context of the task and still use a lot of pre‐interpreted texts (Lennox et al., 2020); teacher candidates implementing NOS in inquiry even though NOS is not required (Librea‐carden et al., 2021); content knowledge and social factors influencing students' moral reasoning (Seiter & Fuselier, 2021); and negotiations in scientific arguments producing group consensus (Governor et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The translation of CRISPR/Cas9 towards in vivo gene editing presents significant challenges that need to be tackled, including concerns regarding specificity, safety, and efficient delivery. Additionally, research studies have raised apprehensions about the promotion of CRISPR/Cas9 applications, touching upon aspects such as safety, ethics, social fairness, and the risks associated with transgenic manipulation [207] , [208] , [209] , [210] . Consequently, it is crucial to establish a comprehensive legal framework that ensures the secure and equitable utilization of gene editing technology.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the non‐scientific aspects of SSC cannot be underestimated. Teachers need to be sensitive to the value of the multiple ways of knowing that students bring to SSI‐based teaching (Balgopal et al, 2017; Hodson, 2020; Seiter & Fuselier, 2021; Tolbert et al, 2018) and they need to “foster classroom environments that encourage the expression of diverse perspectives even when those perspectives are not consistent with traditional notions of science” (Zeidler et al, 2005, p. 369). Awareness of the wide variety of students' SSI‐related resources is necessary in order to adapt SSI‐based teaching and learning to the resources that students bring with them.…”
Section: Discussionmentioning
confidence: 99%
“…When studying knowledge as a student resource in SSI‐related learning and decision‐making, researchers have often focused on prior content knowledge or what is termed school knowledge or subject‐matter knowledge (Baytelman et al, 2020; Christenson & Chang Rundgren, 2015; Sadler & Donnelly, 2006; Sadler & Zeidler, 2005; Seiter & Fuselier, 2021). Prior content knowledge enhances the quality of students' reasoning about SSI (Baytelman et al, 2020; Chang et al, 2020; Lewis & Leach, 2006; Sadler & Zeidler, 2005; Von Aufschnaiter et al, 2008) and has a positive effect on learning gains (Hadjichambis et al, 2016).…”
Section: Socioscientific Capitalmentioning
confidence: 99%